If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(33 + 14x) = 11 * 3x (33 * 2 + 14x * 2) = 11 * 3x (66 + 28x) = 11 * 3x Multiply 11 * 3 66 + 28x = 33x Solving 66 + 28x = 33x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33x' to each side of the equation. 66 + 28x + -33x = 33x + -33x Combine like terms: 28x + -33x = -5x 66 + -5x = 33x + -33x Combine like terms: 33x + -33x = 0 66 + -5x = 0 Add '-66' to each side of the equation. 66 + -66 + -5x = 0 + -66 Combine like terms: 66 + -66 = 0 0 + -5x = 0 + -66 -5x = 0 + -66 Combine like terms: 0 + -66 = -66 -5x = -66 Divide each side by '-5'. x = 13.2 Simplifying x = 13.2
| 2x-10+12=180 | | 11x-10+39+6x+11= | | 4x*x=5*20 | | 2(3x+1)+5(x-4)= | | 9x+8=6x+47 | | 2(p-3)+6=-10 | | g-11=7 | | 6k=6k+48 | | 7x-4=72 | | 2(33+11x+3x)=11*3*X | | sqrt((64b^27)/(27a^15)) | | 6n+8-4n=-20 | | 2(36+9x+4x)=9*4*x | | 118=g-4/2/5 | | 4x=x-8+20 | | -20=-3r-5 | | 7xyz^3-5y^2z^2+1=n | | 5x-2x=7x-2 | | 0.5z=6 | | 2x+8+9x=-80 | | n=2.125+-1.125n | | 3x-5x=8x+10 | | 100=15y+10y | | 0.20*-250+0.30=0.27*-250+25 | | 3-4x=6(2/3x-1/2) | | 5y=15-6x | | 4(r-3)+1=33 | | 5q+14=4 | | 13x+3+85+85+96=180 | | -1=d+21 | | 2(33+11x+3x)=c | | x^2+(-4x-14)(-4x-14)=25 |